Psychometric Properties of an Emotional Communication Questionnaire for Education and Healthcare Professionals - Carmen M. Hernández-Jorge; Antonio F. Rodríguez-Hernández; Olena Kostiv; Francisco Rivero; Raquel Domínguez-Medina (MDPI AG, 2022)
Educational and healthcare professionals need to develop emotional communication with schoolchildren and patients, respectively. This study aims to analyse the psychometric properties of an instrument that evaluates emotional communication among these professionals. A total of 406 professionals and students of education and health sciences took part in the study. They were administered a questionnaire using a Google Form that collected different elements of emotional communication. An exploratory factor analysis was carried out from which three factors were extracted: Communicative Proactivity, Openness and Authenticity, and Listening. These were supported by confirmatory factor analysis. The internal consistency of the scale is also adequate, ranging from 0.69 to 0.82. This instrument is valid, and, in a self-reported, straightforward and time-efficient manner, can assess the emotional communication of professionals and students of education and health sciences.